Pengaruh antara Risiko Bisnis, Strategi Pertumbuhan, Struktur Modal terhadap Kinerja Perusahaan Makanan dan Minuman di Bursa Efek Jakarta - Anwar, Muhadjir (Universitas Brawijaya, Indonesia, 2009)
Performance is form of reached progress by company. Company performance of yielded profit from overall of company operation. Many company in Indonesia having problem degradation of performance, this related with some factor that is business risk, growth strategy, and capital structure. This research aim to know influence between business risk, growth strategy, capital structure, to company performance at company of food and beverage which enlist in Stock Exchange of Jakarta. Population in this research is all company of food and beverage which enlist in Stock Exchange of Jakarta period 2003-2007. Sample in research taken with technique of purposive sampling that obtained 8 company as sample. Data type the used is data of secondary which in the form of financial statement summary company of food and beverage which there are in Indonesian Capital Market Directory 2004 and 2007. Analysis model the used is analysis path use regression standardize Result of research conclude that business risk have an effect on positive to capital structure. Growth strategy have an effect on positive to capital structure. Capital structure have an effect on negativity to performance company of Strategy growth have an effect on negativity to company performance. Business risk not significant to company performance.